There is no such thing as an international ilite under-9 soccer player - Kirkland, A.; O`Sullivan, M. (Journal of Sports Science & Medicine, 2018)
In a recent article published in the Journal of Sports Science and Medicine, Müller and colleagues (2018) presented an article on the relative age effect in international elite under-9 soccer players. Their aim was to investigate the association between biological maturity and the relative age effect in young footballers. Our aim in writing this letter is to highlight theoretical and ethical perspectives, which influenced our beliefs on the contribution to knowledge of this paper